2D bismuthene as a functional interlayer between BiVO4 and NiFeOOH for enhanced oxygen-evolution photoanodes - Cui,J; Daboczi,M; Regue,M; Chin,Y; Pagano,K; Zhang,J; Isaacs,MA; Kerherve,G; Mornto,A; West,J; Gimenez,S; Kim,J; et al. (Advanced Functional Materials, 2022)
BiVO4 has attracted wide attention for oxygen-evolution photoanodes in water-splitting photoelectrochemical devices. However, its performance is hampered by electron-hole recombination at surface states. Herein, partially oxidized two-dimensional (2D) bismuthene is developed as an effective, stable, functional interlayer between BiVO4 and the archetypal NiFeOOH co-catalyst. Comprehensive (photo)electrochemical and surface photovoltage characterizations show that NiFeOOH can effectively increase the lifetime of photogenerated holes by passivating hole trap states of BiVO4; however, it is limited in influencing electron trap states related to oxygen vacancies (VO). Loading bismuthene on BiVO4 photoanodes increases the density of VO that are beneficial for the oxygen evolution reaction via the formation of oxy/hydroxyl-based water oxidation intermediates at the surface. Moreover, bismuthene increases interfacial band bending and fills the VO-related electron traps, leading to more efficient charge extraction. With the synergistic interaction of bismuthene and NiFeOOH on BiVO4, this composite photoanode achieves a 5.8-fold increase in photocurrent compared to bare BiVO4 reaching a stable 3.4 (±0.2) mA cm–2 at a low bias of +0.8 VRHE or 4.7(±0.2) mA cm–2 at +1.23 VRHE. The use of 2D bismuthene as functional interlayer provides a new strategy to enhance the performance of photoanodes.